2020
DOI: 10.1002/cctc.202000794
|View full text |Cite
|
Sign up to set email alerts
|

Affecting the Formation of the Micro‐structure and Meso/macro‐structure of SAPO‐34 zeolite by Amphipathic Molecules

Abstract: SAPO-34 is an important member in the family of zeolites, which shows excellent catalytic activity in MTO reaction, but suffers from the diffusion bottleneck. To overcome the diffusion problem, porogen was added to generate meso/macro pores in SAPO-34 zeolite. In this work, amphipathic molecules were designed as CSDA to synthesize a tri-level hierarchically porous SAPO-34, and the introduction of CSDA could promote the Si atoms incorporating into the AlPO 4 framework, change the morphology of particles and dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…To evaluate the effect of IL loading on the crystal structure of the molecular sieves, XRD was performed on the samples before and after loading, as shown in Figure 3 c. The diffraction peaks indicated that the loaded IL maintained the crystal structure of the pristine SAPO-34, with diffraction peaks at 2θ of 9.56, 12.98, 16.16, 20.76, 26.08, and 31.22° attached to (101), (110), (021), (121), (220), and (401) planes of SAPO-34, respectively. 33 , 34 The peaks are of high intensity, indicating that the loaded IL remains well crystalline and suggesting that the IL deposit does not alter the crystal structure of original SAPO-34.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the effect of IL loading on the crystal structure of the molecular sieves, XRD was performed on the samples before and after loading, as shown in Figure 3 c. The diffraction peaks indicated that the loaded IL maintained the crystal structure of the pristine SAPO-34, with diffraction peaks at 2θ of 9.56, 12.98, 16.16, 20.76, 26.08, and 31.22° attached to (101), (110), (021), (121), (220), and (401) planes of SAPO-34, respectively. 33 , 34 The peaks are of high intensity, indicating that the loaded IL remains well crystalline and suggesting that the IL deposit does not alter the crystal structure of original SAPO-34.…”
Section: Resultsmentioning
confidence: 99%